Avaliação e monitoramento de águas superficiais e minas d’água no entorno do aterro sanitário no município de Cascavel - PR - Dullius, Thaisa (2018)
The objective of this word was to monitor and evaluate the quality of surface waters and water mines in areas at risk of pollution nearby the sanitary landfill in the city of Cascavel - PR. Water samples were collected at nine points around the landfill, which five points were from surface water and four points from water mines. The collections were carried out monthly, during a year, from June 2016 to May 2017. We analyzed the physical and chemical parameters: chloride, hardness, nitrate, odor, color, turbidity, alkalinity, silica, sulfate and pH, and the elemental composition. For the elementary content analysis, the Total reflection X-ray fluorescence spectrometry (TXRF) was used. The results were statistically treated in order to evaluate the similarity and distance in the water characteristics and between the sampling points. In addition, the net accumulation rate, applied to the chemical elements, was shown to be more relevant. The physical-chemical analysis reveals that two points of the water mines present in disagreement as to the color and turbidity for human consumption, while the elemental composition reveals that all the evaluated points are presented in nonconformity due to some element, which the main ones involved are: Mn, Fe, Ni, Cu and Ba. Between them, iron was the most predominant, in disconformity among seven of the nine monitored points. From the cluster analysis, it was verified that the characteristics of upstream and downstream waters differ from the other five monitoring points, and these characteristics are likely to come from different sources. It is also observed that some of the geographically closest points were also the most similar to each other, according to the characteristics obtained. The dendrogram that groups the points of both surface waters and water mines with the raw landfill leachate samples, when correlating them, presumes it is possible to influence on the quality of the water. The PCA showed the behavior of the analyzed parameters, grouping the same factors to those that varied with the same proportion over the months and / or from the monitoring points. The liquid accumulation rate revealed that the chemical elements that presented a cumulative character in surface waters and water mines were: Cl, Ca, Ti, Mn, Ni, Cu and Ba. It can be concluded that the monitored waters are impacted and that the methodology applied in the study, mainly the analysis of grouping, that pointed different sources of alteration in the characteristics of these waters, being one of them, possibly coming from the landfill.